Increased transforming growth factor β and interleukin 10 transcripts in peripheral blood mononuclear cells of colorectal cancer patients - Stanilov, Noyko S.; Miteva, Lyuba; Cirovski, Geo; Stanilova, Spaska A. (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study: The ability of immune cells in peripheral blood to produce certain cytokines affects tumour-elicited inflammation. The aim of this study was to investigate the gene expression of interleukin 12A (IL-12A), IL-12B, IL-23A, IL-10, IL-6, transforming growth factor β (TGF-β), HDAC3, and iNOS in peripheral blood mononuclear cells (PBMC) from colorectal cancer (CRC) patients. Material and methods: The venous blood for PBMC isolation was collected preoperatively and 10 days after surgery, from CRC patients. After isolation of total RNA and synthesis of cDNA, quantitative real-time PCR assays were performed. Results : Our results demonstrated that among investigated cytokine genes IL-10 and TGF-b were significantly upregulated in patients with CRC compared to the control group, while the expression of IL-23 mRNA was significantly decreased in CRC patients. We observed significantly increased mRNA levels in CRC patients’ PBMC before surgery for IL-10 and TGF-b compared to both postoperative and control groups. We also found a significant upregulation of iNOS in early compared to advanced CRC. Conclusions : Based on the results we can assume that PBMC gene expression programming in CRC patients drives local differentiation of Th cells towards Treg instead of the Th1 anti-tumour subpopulation.